Назад
a+b c
1
+c
2
+
. . .+ c
n
d
3
σ = f
n
(P
1
, . . . , P
n
, s)
n
Y
i=1
d
3
p
i
E
i
.
f
n
(P
1
, . . . , P
n
, s) = const
T
r
0
= ¯h/m
π
c
=
4
3
πr
3
0
γ
c
=
γ
c
,
γ
c
= E
/mc
2
E
ε ε (kT )
4
E
Ω(kT )
4
, =
0
γ
c
=
0
mc
2
E
, E
0
mc
2
E
(kT )
4
,
E
2
0
mc
2
(kT )
4
, E
q
0
mc
2
(kT )
2
.
kT
E
n =
E
kT
(E
)
1/2
E
1/4
,
E
E
1/4
n E
1/3
n E
1/2
π
E kT m
π
c
2
.
kT mc
2
N
p
: N
π
= 8: 3
π
π
+
π
π
0
n p ¯n ¯p
1/2
kT m
π
c
2
n E
1/4
.
4 ·10
14
p
= p sin θ = p
sin θ
E
T
E
m 2π 3π 4π 5π 6π
kT
m
π
c
2
p
m
π
c
2
q
a
b
c d a c
b d q
2
= (P
a
P
c
)
2
= (P
b
P
d
)
2
π
P
i
q
i
a
P
1
q
1
P
2
q
2
q
N1
b
hp
i 0.35
ρ
p
x
i
= p
i
/p
i1
< 1;
x
i
p
i
y
i
= y
i+1
y
i
ln[x
i+1
m
i
/m
i+1
],
m
i
y
i
dN/dy const.
dN/dy
hni
Z
y
a
y
b
dN
dy
dy a ln(y
a
y
b
) + b = a ln
s
m
2
+ p
2
+ b.
b
x
i
=
= p
i
/p
i1
< 1
a
y
= 0
s
1
s
2
s
1
< s
2
10
12